The Reaction of Aromatic Aldehydes and 1,3-Cyclohexanedione in Aqueous Media - Liu Li-Bin; Jin Tong-Shou; Han Li-Sha; Li Meng; Qi Na; Li Tong-Shuang (E-Journal of Chemistry)
The reaction of aromatic aldehyde and 1,3-cyclohexanedione in aqueous media has been catalyzed by p-dodecylbenezenesulfonic acid (DBSA) or sodium dodecyl sulfate (SDS) and yields two products: 9-aryl-1, 8-dioxooctahydroxanthene derivatives and 2,2´-arylmethylene bis(3-hydroxy- 2-cyclohexene-1-one). This method provides several advantages such as good yield, simple work-up procedure and environment friendly.